2022
DOI: 10.1007/s40710-022-00585-9
|View full text |Cite
|
Sign up to set email alerts
|

Air Quality during the COVID–19 Lockdown and Unlock Periods in India Analyzed Using Satellite and Ground-based Measurements

Abstract: A nationwide lockdown was imposed in India from 24 March 2020 to 31 May 2020 to contain the spread of COVID-19. The lockdown has changed the atmospheric pollution across the continents. Here, we analyze the changes in two most important air quality related trace gases, nitrogen dioxide (NO 2 ) and tropospheric ozone (O 3 ) from satellite and surface observations, during the lockdown (April – May 2020) and unlock periods (June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 86 publications
(64 reference statements)
0
19
0
Order By: Relevance
“…The reduction in air pollution due to the decline of economic activities during lockdown was reported by many authors across the world (Mousazadeh et al 2021 ) (Supplementary Material ( SM ); Table SM1 ). The positive effect of COVID-19 lockdown on air quality improvement, mainly reduction of NO 2 and CO concentrations, was observed in some parts of India (Allu et al 2021 ; Bera et al 2021 ; Chelani and Gautam 2021 ; Gopikrishnan et al 2022 ), Italy (Collivignarelli et al 2020 ; Gautam 2020 ), China (Chen et al 2020b ; Gautam 2020 ), Spain (Gautam 2020 ; Tobías et al 2020 ; Pey and Cerro 2022 ), France (Gautam 2020 ), Vietnam (Nguyen et al 2022 ), Russia (Ginzburg et al 2020 ), Canada (Tian et al 2021 ), USA (Liu et al 2021 ), Turkey (Şahin 2020 ) and Malaysia (Ash’aari et al 2020 ). However, the impact of lockdown measures was not uniform across different pollutants and areas.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in air pollution due to the decline of economic activities during lockdown was reported by many authors across the world (Mousazadeh et al 2021 ) (Supplementary Material ( SM ); Table SM1 ). The positive effect of COVID-19 lockdown on air quality improvement, mainly reduction of NO 2 and CO concentrations, was observed in some parts of India (Allu et al 2021 ; Bera et al 2021 ; Chelani and Gautam 2021 ; Gopikrishnan et al 2022 ), Italy (Collivignarelli et al 2020 ; Gautam 2020 ), China (Chen et al 2020b ; Gautam 2020 ), Spain (Gautam 2020 ; Tobías et al 2020 ; Pey and Cerro 2022 ), France (Gautam 2020 ), Vietnam (Nguyen et al 2022 ), Russia (Ginzburg et al 2020 ), Canada (Tian et al 2021 ), USA (Liu et al 2021 ), Turkey (Şahin 2020 ) and Malaysia (Ash’aari et al 2020 ). However, the impact of lockdown measures was not uniform across different pollutants and areas.…”
Section: Introductionmentioning
confidence: 99%
“…14 NO x levels in the troposphere can alter ozone formation, contribute to nitrate aerosol formation, and acid deposition and affect climate cycles. 15,16 In addition to its effects on climate, a study over the U.S. showed that NO 2 with levels above the annual average limit of 53 ppb can cause ailments including asthma, bronchitis and pneumonia. 17,18 A comparison of pollutant-wise highest health risk values shows that NO 2 is about 25.25 times more risky than SO 2 , whereas the health risk due to suspended PM is about 19.27 times more than that due to SO 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, during the Covid-19 lockdown, satellite measurements showed a substantial reduction in NO 2 due to restrictions imposed over its major sources such as transportation, the power sector and industries. 16,38 A systematic inventory made by Garg et al 39 on various sources of NO 2 emission in India showed that 50% of NO 2 pollution is from industries, 32% from transportation and 10-20% from biomass burning. A global analysis with gridded emissions of air pollutants by Crippa et al 40 revealed that India had shied to signicant emitters of NO x from 1970 to 2012 with emissions of 11 Mt.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations